A glutathione responsive nanocarrier based on viologen resorcinarene cavitand and 1-allylthymine. (14th June 2022) - Voloshina, Alexandra D.; Mansurova, Elina E.; Bakhtiozina, Leysan R.; Shulaeva, Marina M.; Nizameev, Irek R.; Lyubina, Anna P.; Amerhanova, Syumbelya K.; Kadirov, Marsil K.; Ziganshina, Albina Y.; Semenov, Vyacheslav E.; Antipin, Igor S.
Abstract : A glutathione-sensitive nanocarrier for doxorubicin to improve cellular penetration and selective cytotoxic effects on T98G human glioblastoma cells. Abstract : This article presents a simple and original approach to developing a redox-sensitive nanocarrier for the anticancer drug doxorubicin. The approach is based on microemulsion copolymerization of viologen resorcinarene acrylate and allylthymine with a dispersed phase, diallyl disulfide. During polymerization, diallyl disulfide forms a redox-sensitive core copolymerized on the surface with viologen resorcinarene acrylate and allylthymine. The obtained nanocarrier has a size of about 50–60 nm and is highly stable in aqueous media, and its decomposition occurs at an increased concentration of glutathione. The nanocarrier improves the penetration of doxorubicin into cells, while the doxorubicin encapsulated in the nanocarrier demonstrates selective cytotoxicity towards T98G human glioblastoma cells.